COMMON OWNERSHIP OF SPOUSES (Analysis of the Georgian Civil Law) (Law and world, 2020)
The research shows that one of the legal relations in civil matters is the family relationship, having an extensive content. It includes Family Law and the actual family relationships. While there are factual elements in the family relationships, only marriage registration gives rise to the property and personal rights between spouses since marriage is a legal fact of law. However, it has been stated correctly in the legal literature that the actual co-existence of partners is such a family relationship, in which couples enter into marriage without registration. The inner world of unmarried couples is significantly free from legal regulation. Family relationships, by their characteristics, are inconceivable without the personal and intimate aspects contained in certain factual foundations and found in family relationships.